46.0k views
2 votes
Help asap lol please thanks!

Help asap lol please thanks!-example-1
User Smolo
by
6.3k points

1 Answer

0 votes

Answer:

-11/12

Explanation:

Solve each fraction expression on the numerator and denominator separately.

5/8 + 3/4 = 5/8 + 6/8 = 11/8

-2/3 - 5/6 = -4/6 - 5/6 = -9/6 = -3/2

Now we have (11/8) / (-3/2). We solve this by flipping the denominator fraction and multiplying that by 11/8.

[Flip -3/2] -2/3

11/8 x -2/3 = -11/12

Hope this helps!

User Srgsanky
by
5.8k points